The Effect of Artistic Taste on the Change of Contemporary Kurdish Interior’s Space Elements Case study: Living Spaces in Sulaymania Modern Houses - Ali, Amjad M.; Abdullah, Tablo Nawzad (Sulaimani Journal for Engineering Sciences, 2019)
The factors of personality and socio-cultural upbringing of the Kurdish individual generated an interior environment with unique attributes. This unique interior environment brought about a collective perspective that is reflected in the Kurdish house environment. Yet, the interior environment of the Kurdish home has changed in response to changes in means of living and a variety of factors affecting it, in the cultural, social, and technological context of the Kurdish society. The traditional elements of the Kurdish house’s interior space are disappearing precipitately. New elements, relations, and styles are filling their places in the design of the interior space that are strange to the traditional ways . This study raises questions about the rapid and far reaching changes that the components of the interior environment of the Kurdish house have witnessed, and links them to the aesthetic tastes of the Kurdish personality, as the factor that is most expressive of the Kurdish mentality and psychology, which is the artistic taste of the Kurdish personality, and also asking about the impact of artistic taste of the Kurdish personality in that change. The research aims to link the vocabulary of taste and the Kurdish personality to the internal spaces of the Kurdish houses, and then to know the extent of the influence of the artistic taste factors in the change in the internal elements of the Kurdish houses, assuming the difference of the influence of artistic taste in the change in the elements of the internal spaces of the Kurdish houses, influenced by Kurdish personality factors. The research concluded that aesthetic and artistic tastes have a different effect on the selection of interior design elements. Specific factors affect the selection of a particular design regardless of aesthetic values, while other factors are influenced by the values and aesthetic criteria in the selection of interior design elements in the Kurdish house.
Keywords: Artistic taste; Interior Design; Kurdish House; Kurdish Architecture